2022
DOI: 10.1186/s12879-022-07519-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of COVID-19 admissions in a population with a high prevalence of HIV and tuberculosis: a multicentre cohort study

Abstract: Background There is still a paucity of evidence on the outcomes of coronavirus disease 2019 (COVID-19) among people living with human immunodeficiency virus (PWH) and those co-infected with tuberculosis (TB), particularly in areas where these conditions are common. We describe the clinical features, laboratory findings and outcome of hospitalised PWH and human immunodeficiency virus (HIV)-uninfected COVID-19 patients as well as those co-infected with tuberculosis (TB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
0
6
0
1
Order By: Relevance
“…concluded that higher values of CRP were measured in patients diagnosed with all three infections: TB, HIV, and COVID-19 ( 67 ). However, researchers recommend CRP as a monitoring and prognosis tool in patients diagnosed with both TB and COVID-19, rather than as a rule-out screening test ( 68 ). Multiple investigations are required in order to generalize our results in those individuals.…”
Section: Discussionmentioning
confidence: 99%
“…concluded that higher values of CRP were measured in patients diagnosed with all three infections: TB, HIV, and COVID-19 ( 67 ). However, researchers recommend CRP as a monitoring and prognosis tool in patients diagnosed with both TB and COVID-19, rather than as a rule-out screening test ( 68 ). Multiple investigations are required in order to generalize our results in those individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This cohort’s prevalence of HIV infection was within the range for other reported estimates and is likely to be broadly representative of similar hospital cohorts in South Africa. 6 , 41 , 42 Approximately one-third of PLWH in this study did not have HIVVLs measured which may have biased the comparison between detectable versus undetectable HIVVL participants. Strengths of our study include prospective data collection, a validated method for quantifying respiratory disease severity on a continuum, many patients with laboratory biomarkers during admission, and PLWH well characterised in terms of other comorbidities.…”
Section: Discussionmentioning
confidence: 97%
“…Although there was a trend toward increased rates of ICU admission, mechanical ventilation, and mortality in PWH compared with their HIV-uninfected counterparts, these outcomes were not statistically significant within their small sample size. Another study from South Africa compared patients with and without HIV who were hospitalized with COVID-19 and did not find a clear increase in mortality associated with HIV, though having a CD4 cell count less than 200 cells/μl was a separate mortality risk factor [10 ▪ ].…”
Section: Severity Of Coronavirus Disease 2019 In Individuals With Wel...mentioning
confidence: 97%
“…An exploratory subgroup analysis of the recent large WHO Clinical Platform study found that HIV RNA greater than 1000 copies/ml and CD4 cell count less than 200 cells/ml nearly doubled the risk of in-hospital mortality compared with those with well controlled HIV [18 & ]. Another cohort study from South Africa also found that CD4 cell count less than 200 cells/ml was independently associated with increased risk of COVID-19 mortality [10 ]. A third recent South African cohort study found that among PWH, COVID-19 mortality was associated with lower recent CD4 count, high HIV RNA, and no evidence of recent antiretroviral prescription [19…”
Section: Key Pointsmentioning
confidence: 99%